Surviving a zombie apocalypse: Leadership configurations in extreme contexts. Issue 2 (April 2019) - Buchanan, David A; Hällgren, Markus
What can the classic zombie movie, Day of the Dead, tell us about leadership? In our analysis of this film, we explore leadership behaviours in an extreme context – a zombie apocalypse where survivors face persistent existential threat. Extreme context research presents methodological challenges, particularly with regard to fieldwork. The use of films as proxy case studies is one way in which to overcome these problems, and for researchers working in an interpretivist perspective, 'social science fiction' is increasingly used as a source of inspiration and ideas. The contribution of our analysis concerns highlighting the role of leadership configurations in extreme contexts, an approach not previously addressed in this field, but one that has greater explanatory power than current perspectives. In Day of the Dead, we observe several different configurations – patterns of leadership styles and behaviours – emerging, shifting and overlapping across the phases of the narrative, each with radically different consequences for the group of survivors. These observations suggest a speculative theory of leadership configurations and their implications in extreme contexts, for exploring further, with other methods.